IOT-Driven Smart Energy Monitoring: Development of Simonde in Telecommunication Laboratory - Ade Irfansyah; Yuyun Suprapto; Nyaris Pambudiyatno; Bambang Bagus Hariyanto; Teguh Imam Suharto (Letters in Information Technology Education (LITE), 2025)
Accurate electrical energy monitoring is essential for effectively managing its usage. The Internet of Things (IoT) technology offers an optimal solution for real-time monitoring. This study aims to design and implement an IoT-based Power and Energy Monitoring System (SiMONDE) that efficiently monitors electrical energy usage in a telecommunications laboratory in real-time. The research employs a research and development methodology with the ADDIE model approach, encompassing three phases: (1) analysis, (2) design, and (3) development. The results indicate significant errors in SiMONDE when measuring current in the range of 0.3 to 0.12 Amperes, compared to a clamp meter. However, when measuring currents between 1.6 and 3.7 Amperes, SiMONDE exhibits a low error margin. Additionally, SiMONDE's media feasibility and usage feasibility percentages are 97.5% and 96.87%, respectively. The study concludes that SiMONDE is not sufficiently accurate for low-current measurements, yet demonstrates high usability feasibility according to user needs.